Solvent polarity scales: determination of new ET(30) values for 84 organic solvents. (19th February 2014) - Cerón‐Carrasco, José P.; Jacquemin, Denis; Laurence, Christian; Planchat, Aurélien; Reichardt, Christian; Sraïdi, Khadija
<x xml:space="preserve">Abstract</x> The solvent polarity parameter ET(30) is newly measured from the solvatochromism of the betaine dye 30 for 84 solvents and re‐measured for 186 additional ones. The results are organized in a database. It is shown that the validity of linear solvation energy relationships used for the determination of secondary ET(30) values is limited to non‐hydrogen‐bond donor solvents. Relationships with the chain length n are given for the determination of tertiary ET(30) values of the homologous H(CH2)nY solvent series. The parameter ET(30) is orthogonal to the function of the refractive index (n2 − 1) / (2n2 + 1). For non hydrogen‐bond donor solvents, this allows to enter ET(30) as an almost pure electrostatic parameter in a new linear solvation energy relationship. Copyright © 2014 John Wiley & Sons, Ltd.